Valence electron distribution in zirconium dodecaboride - Filippov, V.B.; Paderno, Yu.B.; Belogovskii, M.A.; Gusev, A.A.; Felner, I. (Functional Materials, 2006)
First-principles calculations of the valence electron distribution in ZrB₁₂ have been performed by the modified Thomas-Fermi statistical method. The charge destiny maps for some planes across Zr and B atoms are presented and discussed. Directional bonding intoduced by born atoms in the crystal lattice explains the superhardness of the material.